Art Without Boundaries - Thompson, Philip; Williams, John; Woods, Gerald (New York / Washington : Praeger Publishers, 1974)
The most exciting and possibly the most fruitful, trend in the visual arts since the early 1950s has been the steady erosion of traditional boundaries : between painting and sculptures, painting and film, film and typography, photography and print-making, Fine and Commercial art. Rauschenberg began to silkscreen photographic halftones directly onto canvas. Hansjorg Mayer, and others, experimenting in autonomous typography, created Concrete Poetry : Antonioni Painted with film and Godard interspliced verbal messages with film sequences. The photography of Brandt, De Maré, and Raymond Moore must be judged by the same standards as the work of a painter, however different their aims, Christo's wrapped objects and Boyle's Happenings show how art can be extended into our environment and our lives. These and other developments are ably illustrated in this book, which includes the work of over seventy artists drawn from many countries. Each artist is also represented by a statement of his aims (often in his own words) and a biography.
Adami, Valerio ; Antonioni, Michelangelo ; Bailey, Dennis ; Bass, Saul ; Beall, Lester ; Bill, Max ; Birdsall, Derek ; Bons, Jan ; Borowczyk, Walerian ; Boyle, Mark ; Brandt, Bill ; Brownjohn, Robert ; Burri, Alberto ; Bury, Pol ; Calman, Mel ; Carena, Antonio ; Carmi, Eugenio ; Ceroli, Mario ; Chermayeff, Ivan ; Christo ; Chryssa ; Cieslewicz, Roman ; Cittato, Giulio ; Cobbing, Bob ; Crosby, Theo ; Crouwel, Wim ; D'Arcangelo, Allan ; Fellini, Federico ; Fletcher, Alan ; Folon, Jean-Michel ; Fontana, Lucio ; Forbes, Colin ; Francois, André ; Froshaug, Anthony ; Gale, Geoffrey ; Gallina, Pietro ; Gallo, Frank ; Gaul, Winfred ; Geismar, Thomas H. ; Genoves, Juan ; Godard, Jean-Luc ; Grignani, Franco ; Hamilton, Richard ; de Harak, Rudolph ; Higgins, Dick ; Hockney, David ; Houédard, Dom Sylvester ; Kaine, John ; Klein, William ; Kriwet, Ferdinand ; Lenica, Jan ; LeWitt, Sol ; De Maré, Eric ; de Maria, Walter ; Marmer, Romek ; Massin, Robert ; Moore, Raymond ; Müller-Brockmann, Josef ; Odermatt, Siegfried ; Oldenburg, Claes ; Pintori, Giovanni ; Pistoletto, Michelangelo ; Rand, Paul ; Rauschenberg, Robert ; Raveel, Roger ; Robbe-Grillet, Alain ; Roth, Dieter ; Schleger, Hans ; Schmidt, Peter ; Smith, Richard ; Themerson, Stefan ; Tschichold, Jan ; VanDerBeek, Stan ; Wesselmann, Tom ; Wirth, Kurt ; Wolf, Henry ; Wright, Edward
Biog. p. 201-214
Engels
kunstcatalogus